Ghrelin function in human obesity and type 2 diabetes: a concise review. (29th November 2016) - Churm, R; Davies, JS; Stephens, JW; Prior, SL
Summary: The 28 amino acid hormone, ghrelin, has been found to have various effects on metabolism. This review will focus on the pathways integrated into ghrelin's effect within the hypothalamus, pancreas and adipocytes. The identification of molecules and pathways that regulate ghrelin‐mediated lipid retention could establish new mechanisms underlying cellular energy homeostasis. The impact of acyl‐ghrelin on glucose metabolism and lipid homeostasis may allow for novel preventative or early intervention therapeutic strategies to treat obesity related type 2 diabetes and associated metabolic dysfunction.